AKTIVITAS OTAK MEMICU KEMAHIRAN BERBAHASA ANAK: KAJIAN NEOROLOGI - Asri Yulianda; Shopiah Anggraini Rambe; Anna Leli Harahap; Ratih Rindyani (JURNAL EDUCATION AND DEVELOPMENT, 2024)
This study aims to describe brain development in children's language skills. This type of research is a qualitative research that examines the language skills of early childhood in a neurolinguistic way. The object of this study were 2 boys and 2 girls with different parenting styles. Data collection techniques were carried out directly and direct interviews with the child's parents. The results showed that parental factors greatly influenced the development of children's language skills. Parents must be patient when they have to teach their children many things, establishing 2-way communication can help children withstand brain development. The mistakes of parents that hinder the development of their children's language, such as not playing with children, rarely inviting children to communicate, exemplifying slurred speech, introducing gadgets from infancy, rarely reading story books to children.